Using bifactor exploratory structural equation modeling to examine global and specific factors in measures of sports coaches' interpersonal styles - Stenling, Andreas; Ivarsson, Andreas; Hassmén, Peter; Lindwall, Magnus (Frontiers in Psychology, 2015)
In the present work we investigated distinct sources of construct-relevant psychometric multidimensionality in two sport-specific measures of coaches’ need-supportive (ISS-C) and controlling interpersonal (CCBS) styles. A recently proposed bifactor exploratory structural equation modeling (ESEM) framework was employed to achieve this aim. In Study 1, using a sample of floorball players, the results indicated that the ISS-C can be considered as a unidimensional measure, with one global factor explaining most of the variance in the items. In Study 2, using a sample of male ice hockey players, the results indicated that the items in the CCBS are represented by both a general factor and specific factors, but the subscales differ with regard to the amount of variance in the items accounted for by the general and specific factors. These results add further insight into the psychometric properties of these two measures and the dimensionality of these two constructs.